Offline Parietal Intermittent Theta Burst Stimulation or Alpha Frequency Transcranial Alternating Current Stimulation Has No Effect on Visuospatial or Temporal Attention - Moretti, Jessica; Marinovic, Welber; Harvey, Alan R.; Rodger, Jennifer; Visser, Troy A. W. (Frontiers in Neuroscience, 2022)
Non-invasive brain stimulation is a growing field with potentially wide-ranging clinical and basic science applications due to its ability to transiently and safely change brain excitability. In this study we include two types of stimulation: repetitive transcranial magnetic stimulation (rTMS) and transcranial alternating current stimulation (tACS). Single session stimulations with either technique have previously been reported to induce changes in attention. To better understand and compare the effectiveness of each technique and the basis of their effects on cognition we assessed changes to both temporal and visuospatial attention using an attentional blink task and a line bisection task following offline stimulation with an intermittent theta burst (iTBS) rTMS protocol or 10Hz tACS. Additionally, we included a novel rTMS stimulation technique, low-intensity (LI-)rTMS, also using an iTBS protocol, which uses stimulation intensities an order of magnitude below conventional rTMS. Animal models show that low-intensity rTMS modulates cortical excitability despite sub-action potential threshold stimulation. Stimulation was delivered in healthy participants over the right posterior parietal cortex (rPPC) using a within-subjects design (n=24). Analyses showed no evidence for an effect of any stimulation technique on spatial biases in the line bisection task or on magnitude of the attentional blink. Investigation of individual variability did not support task performance following sham stimulation as a predictor for stimulation effects. Our results suggests that rTMS and LI-rTMS using iTBS protocol and 10Hz tACS over rPPC do not modulate performance in tasks assessing visuospatial or temporal attention.